1999
DOI: 10.1083/jcb.146.5.955
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization and Neurotrophins Converge on the Phosphatidylinositol 3-Kinase–Akt Pathway to Synergistically Regulate Neuronal Survival

Abstract: In this report, we have examined the mechanisms whereby neurotrophins and neural activity coordinately regulate neuronal survival, focussing on sympathetic neurons, which require target-derived NGF and neural activity for survival during development. When sympathetic neurons were maintained in suboptimal concentrations of NGF, coincident depolarization with concentrations of KCl that on their own had no survival effect, synergistically enhanced survival. Biochemical analysis revealed that depolarization was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
184
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(191 citation statements)
references
References 52 publications
6
184
1
Order By: Relevance
“…24,40,42 Membrane depolarization has been shown to activate the PI3K-Akt signaling in neuronal cells. 43,44 Link et al 45 have reported that TRPV2 activity induces membrane depolarization during immune complex-induced phagocytosis. We hypothesized that the influx of Na þ through Trvp5/6 under the low [Ca 2 þ ] condition may lead to membrane depolarization, which in turn increases IGF signaling in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…24,40,42 Membrane depolarization has been shown to activate the PI3K-Akt signaling in neuronal cells. 43,44 Link et al 45 have reported that TRPV2 activity induces membrane depolarization during immune complex-induced phagocytosis. We hypothesized that the influx of Na þ through Trvp5/6 under the low [Ca 2 þ ] condition may lead to membrane depolarization, which in turn increases IGF signaling in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…39 The kinase activity of Akt is sustained by phosphorylation on Ser-473 by upstream kinases. This site is rapidly dephosphorylated after the induction of apoptosis by potassium deprivation.…”
Section: Neurons Overexpressing Tau Preserve a High Level Of P-akt Dumentioning
confidence: 99%
“…Akt (also known as protein kinase B) is a serine/threonine protein kinase that transduces intracellular anti-apoptotic signals that are mediated by serum or growth factors that activate phosphoinositide 3-kinase, or PI3-kinase (Franke et al, 1995;Datta et al, 1997;Dudek et al, 1997;Kennedy et al, 1997;Coffer et al, 1998;Downward 1998;Nunez and del Peso, 1998;Goswami et al, 1999;Kennedy et al, 1999;Flores et al, 2000). Overexpression of Akt prevents apoptosis in certain cells, including neurons, following withdrawal of serum or growth factors (Yao and Cooper, 1995;Datta et al, 1997;Dudek et al, 1997;Crowder and Freeman, 1998;Eves et al, 1998;Ulrich et al, 1998;Bhave et al, 1999;Vaillant et al, 1999;Virdee et al, 1999;Flores et al, 2000;Kermer et al, 2000). The precise mechanisms by which Akt promotes cell survival are not entirely clear.…”
Section: Therapeutic Interventions: Delivery Of Anti-apoptotic Genes mentioning
confidence: 99%